Devastating Postpartum Complications in an Adolescent Linked to New-Onset Inflammatory Bowel Disease and Antiphospholipid Antibody Syndrome. Issue 3 (22nd August 2021) - Rao, Anita; Runde, Joseph; Olivas, Andrea D.; Patton, Tiffany
Abstract : Pregnancy can affect the severity of inflammatory bowel disease (IBD), and pregnant women with IBD are at a higher risk for venous thromboembolism compared with the general population. We report a previously healthy 16-year-old female who developed bloody diarrhea and venous thromboembolism following childbirth, with further evaluation revealing IBD and antiphospholipid antibody syndrome. This case highlights the impact pregnancy can have on IBD and other immunological disorders, and the potentially life-threatening risk of thrombosis in pregnant women with IBD.